THE BIKE ESCAPE - Deary, Terry; De la Rue, James (London : A. & C. Black, an imprint of Bloomsbury Publishing Plc, 2015)
Stories of the Second World War on the Home Front from the bestselling Terry Deary, author of the hugely successful Horrible Histories. A young tearaway unwillingly evacuated to the countryside is unjustly accused of theft. He decides to make his way back home, never mind the Blitz?but he'll need to steal a bike to do it ..
Keywords: World War, 1939-1945 -- Great Britain -- Juvenile fiction; Bicycles -- Juvenile fiction; Theft -- Juvenile fiction; Historical fiction